Saving For The Rainy Day: Penyuluhan Pengelolaan Keuangan dan Investasi Pada Masyarakat Desa Segaran, Delanggu, Klaten, Jawa Tengah - Muhamad Bagus Nurrohman; Cynthia Puspita Ningrum; Indri Siti Mulyani; Yossyca Febri Damayanti; Agni Astungkara (Universitas Maritim AMNI Semarang, 2023)
A country's economic indicators can be seen from the level of public awareness regarding investment and saving. UNIBA Surakarta Community Service is held in Segaran Delanggu with the aim of providing literacy regarding financial management to the general public, starting from early childhood to adulthood. The method used is to approach the community through socialization and provide directions and provide examples that are easy to understand. There are three stages in community service, including the planning stage, the implementation stage, and the evaluation stage. From the activities that have been carried out by the service team, it can show results with an increase in community understanding and awareness of the importance of investment, especially gold and land investment. In addition, there is an increase in the interest of young children to save by setting aside the pocket money they have. With the education that has been given when the activities are carried out, it is hoped that the community will be able to manage their finances better.